Modeling and simulation of bond-wire inductors for high frequency fully integrated switched-mode DC-DC converters - Hao, Guanlong (2018)
In the current semiconductor industry, the technology of semiconductor is more advanced and the size of device get more and more small, as described by the Moore’s Law. To realize the chip fully integration, it will be an excellent choice to use bond-wire which has high quality factor, large cost reduction and power efficiency. Our research group is working on high-frequency fully integrated switched-mode DC-DC converters. However, due to the small diameter and length of the bond-wire, the inductance may be too small and cannot meet the requirement in high-frequency fully integrated switched-mode DC-DC converters. This Master of engineering dissertation project pertains to the work of modeling, designing and realizing high quality factor (Q) and enough value of bond-wire inductors for high frequency fully integrated switched-mode DC-DC converters. The bond-wire inductors are modeled using Ansoft Q3D Extractor tool in the frequency range of 1Hz-1GHz, mainly at 100MHz. The simplified model and advanced model simulation results are verified and get a high Q-factor.